A new pediatric liver transplantation program in Southern Germany: the Heidelberg experience - Engelmann, Guido; Schmidt, Jan; Weitz, Jürgen; Flechtenmacher, Christa; Schenk, Jens-Peter; Weigand, Markus A.; Lenhartz, Henning; Wenning, Daniel; Holland-Cunz, Stefan; Hoffmann, Georg F.; Martin, Eike; Büchler, Markus W.; et al. (Pediatric transplantation, 2010)
PLTx is a highly complex procedure. It can only be performed safely by experienced teams. Starting a new pLTx program in a country with established centers must therefore avoid a learning curve. We have initiated a liver transplantation program for children in 2003. Medical standards were defined by a team of surgeons, pediatricians, radiologists, anesthesiologists, and pathologists before the first transplantation. An external expert in the field of pLTx supervised the whole process. In a pilot phase, six children weighing more than 20 kg were successfully transplanted. Following this series, the clinical pathways were re-evaluated, and the program was opened for children of all age groups. Between 2003 and 2008, 32 children received 34 organs. Sixty-eight percent of patients received a split-liver, 26% a full size organ, and 6% a reduced size graft. Four LRLTx were performed. Patient survival rate was 91%. We conclude that a new pLTx program can be established without a significant learning curve regarding mortality if a strict strategy of team-building is followed. In the pilot phase, small children and infants have to be referred and transplanted in an established center. An interdisciplinary team of specialists closely working together is the key for sustained success.